On the modal response of mobile cables. (1st May 2020) - Bertrand, C.; Plut, C.; Savadkoohi, A. Ture; Lamarque, C.-H.
Abstract: The paper presents methodologies for tracing modal responses of a translating cable. Governing system equations are obtained based on perturbation of the response around the stationary position of the translating catenary. Then, after separation of spatio-temporal system variables, a multiple scale method is endowed for treatment of equations in space. Frequencies and mode shapes of the system are detected by imposing solvability conditions on the system equations and/or via expansion of system variables in the form of Fourier series accompanied by imposing the existence of non-trivial solutions. Finally, obtained results are confronted with those which are obtained by finite difference method.